Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3892/ijmm.2014.1981
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/AKT/PTEN pathway as a target for Crohn’s disease therapy (Review)

Abstract: The pathogenesis of inflammatory bowel disease (IBD), including Crohn's disease, is a subject of increasing interest. Loss-of-function mutations in nucleotide-binding oligomerization domain-containing protein 2 (NOD2) are strong genetic factors linked to Crohn's disease, which eventually leads to an excessive mucosal inflammatory response directed against components of normal gut microbiota. Reactive oxygen species (ROS) play an important role in inflammation processes, as well as in transduction of signals fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 75 publications
(82 reference statements)
1
54
0
Order By: Relevance
“…Furthermore, there was no overlap between the PTEN expression levels in inflamed colonic mucosa of CD patients, compared to non-inflamed CD mucosa, suggesting PTEN as a marker for inflammatory response in colonic CD mucosa. PTEN is described to play a role in the regulation of intestinal permeability [32, 33], and is also defined as a tumor suppressor molecule inhibiting inflammatory response, cell migration, and proliferation via PI3K/Akt pathway [34, 35]. An increased level of microRNA-21 has been described in colonic biopsies from UC patients, compared to normal colonic mucosa, and expression of microRNA-21 in the Caco-2 cell line, a colonic epithelial cell model, resulted in an increased permeability [36].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there was no overlap between the PTEN expression levels in inflamed colonic mucosa of CD patients, compared to non-inflamed CD mucosa, suggesting PTEN as a marker for inflammatory response in colonic CD mucosa. PTEN is described to play a role in the regulation of intestinal permeability [32, 33], and is also defined as a tumor suppressor molecule inhibiting inflammatory response, cell migration, and proliferation via PI3K/Akt pathway [34, 35]. An increased level of microRNA-21 has been described in colonic biopsies from UC patients, compared to normal colonic mucosa, and expression of microRNA-21 in the Caco-2 cell line, a colonic epithelial cell model, resulted in an increased permeability [36].…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylated AKT (pAKT) is able to regulate a large number of downstream targets including transcription factors (reviewed in Manning and Cantley 2007; Faes and Dormond, 2015). PI3K/AKT pathway is considered as a target in the therapy of IBDs such as Crohn's Disease (Tokuhira et al, 2015). IL-6 induces phosphorylation of AKT through PI3K pathway in Caco-2 cells and increases TJs permeability (Suzuki et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the HMGA2 3′UTR has many regulatory sequences which are targeted by different families of miRNAs [19], and it is thought that miRNA-dependent repression is the main mechanism for controlling HMGA2 expression [1214]. Another piece of evidence for the importance of the interaction between HMGA2 and miRNAs is the many disrupted forms of HMGA2 , due to rearrangements of chromosomal band 12q15, that are seen in different benign mesenchymal tumors [2022].…”
Section: Discussionmentioning
confidence: 99%
“…The gene is assumed to be involved in several different tumorigenic processes from cellular proliferation to epithelial-mesenchymal transition and invasive growth [11]. Lately, the role of specific miRNAs has been highlighted in the regulation of HMGA2 expression in neoplastic cells [1214]. MicroRNAs are non-coding RNAs with diverse biological functions [15].…”
Section: Introductionmentioning
confidence: 99%